A SEMIOTIC ANALYSIS OF SUMPAH POCONG AMONG MADURANESE PEOPLE: A CASE STUDY OF POLAGAN DISTRICT, SAMPANG-MADURA - Mukarromah Mukarromah (Lakon : Jurnal Kajian Sastra dan Budaya, 2021)
Abstract: Sumpah pocong is a tradition that is still performed by the Madurese community, especially in the Polagan Village, Madegan, Sampang. This study aims to seek the meaning contained in sumpah pocong based on the signs in sumpah pocong also the concept of signifier and signified by Ferdinand de Saussure. The method used in this research is descriptive qualitative by utilizing field studies through interviews and direct documentation in Polagan Village. The results of this study indicate that the community has different opinions and views in interpreting sumpah pocong.